Effect of Napier grass ensiled with or without inclusion of soy waste on the performance of growing goats (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
Utilization of soy waste as a ruminant feed is low due to storage problems and transportation costs. An experiment was carried out with fifteen goats to assess the feeding value of Napier grass (Pennisetum purpureum) ensiled with or without soy waste. Grass ensiled without soy waste was termed as NM silage, while grass ensiled 30% soy waste (w/w) was termed as NMS silage. In both silages, 1.0% molasses (w/w) were incorporated to enhance the fermentation process. After 2months of ensiling, three diets were formulated and assigned to one of three groups: (i) Napier grass ad libitum plus 1% pellet of body weight (BW) on a dry matter (DM) basis (T1), (ii) NM silage ad libitum plus 1% soy waste of BW on a DM basis (T2), and (iii) NMS silage ad libitum (T3). The NMS silage showed a lower pH (4.04 vs. 4.64) than NM silage. The NMS silage exhibited higher proportions of DM, organic matter (OM), and crude protein (CP) compared to NM silage. Animalsreceived T1 diet showed higher (p
Keywords: Goats; growth performance; intake; silage; soy water